If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -1 = 4(x + -1) Reorder the terms: -1 + 6x = 4(x + -1) Reorder the terms: -1 + 6x = 4(-1 + x) -1 + 6x = (-1 * 4 + x * 4) -1 + 6x = (-4 + 4x) Solving -1 + 6x = -4 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -1 + 6x + -4x = -4 + 4x + -4x Combine like terms: 6x + -4x = 2x -1 + 2x = -4 + 4x + -4x Combine like terms: 4x + -4x = 0 -1 + 2x = -4 + 0 -1 + 2x = -4 Add '1' to each side of the equation. -1 + 1 + 2x = -4 + 1 Combine like terms: -1 + 1 = 0 0 + 2x = -4 + 1 2x = -4 + 1 Combine like terms: -4 + 1 = -3 2x = -3 Divide each side by '2'. x = -1.5 Simplifying x = -1.5
| 4+m=35 | | .5x+.07=.25x+.57 | | -7/13p=-4 | | x^4-4x^3-30x^2-8x-64=0 | | 4x-2=102 | | -6n+-2=16 | | 5r(8r-5)(5r-1)=0 | | 3+8X= | | 19x-5=11x-21 | | 4x+10=3(2x+5) | | 5(12w+1)= | | 16-3.4d=-8 | | 9+3=612 | | 7x+2=3(3x+1) | | 8n-12=40 | | (7+x)/2+3=12 | | 155*22/31*18/25 | | 5a-12=88 | | 9/8*4/5 | | 12-(4m+4)=3+3m-16 | | 2(x-5)+1=-(x+3) | | 7x-24=54 | | -2*(3x-1)-3=-4 | | -0.5x+4.21=0.3x+8.41 | | 6/7*14/27*9/10 | | x-2/3=5-x/2 | | x+16=100 | | 0.5x-0.7x+6=8 | | 1/4*4/3 | | x+1/5=2x-3/4 | | -0.03x=3.3 | | 4/35*5/36 |